Wszystko moze sie przytrafic - Lozinski, Marcel (Poland : Telewizja Polska, 1995)
Tomek, the director's six-year-old son, makes friends with some old people sitting on a park bench. Naiveté and curiosity confront experience. This is a film essay about initiation, bitterness, the passage of time, and life's power.